New Media: Analisis Kritik Netizen terhadap Kampanye Politik Identitas Ganjar Pranowo melalui Azan Stasiun TV pada Media Sosial TikTok - Hazri, Baiq Marcelina Geovani; Yasmin, Adelina Putri; Adha, Dwiki Elryan; Purba, Ridho Ananda; Efendi, Erwan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is ready to participate in the simultaneous elections in 2024. Concerns ahead of the elections revolve around political identity issues, which have been a recurring theme in various elections in the country, including presidential, legislative, and regional head elections. Political actors utilize mass media to build public trust and shape their image in the eyes of the public. TikTok, a popular social media application with over 689 million users worldwide as of January 2021, has become a platform for expressing both supportive and opposing comments regarding the presidential candidates in 2024. This research uses qualitative research methods with a descriptive approach, with the main data source being the TikTok social media platform. The research data consists of netizen comments containing criticism related to political identity issues. Data collection for this research involves documenting screen responses to netizen comments expressing criticism of political identity. The research findings explain how netizens respond to political identity issues.